Spray Performances and Cryogenic Characteristics of C02 Snow under Cryosurgery Guided by Endoscopic. (22nd May 2014) - Lin, T.-C.; Shen, Y.-J.; Wang, M.-R.
ABSTRACT This research experimentally investigated effects of injection pressure, formation chamber and bypass flow on spray performances and cryogenic characteristics of CO2 snow under cryosurgery guided by endoscopic. Results show that CO2 snow has a superior freezing capability in the application of cryosurgery. The length of formation chamber is an effective design parameter to control spray performances and cryogenic characteristics. Increase in the length of formation chamber can increase snow size and conversion ratio, as well as the cooling rate and impact area of the tissue. Thus, it is suitable for the application on wider range nidus. Moreover, the bypass flow can efficiently modulate the cooling effect of the main flow with CO2 snow particles, and extend the operation time of cryosurgery. The experimental results also show that decrease the cylinder pressure, decrease the length of formation chamber, and increase the diameter of bypass apertures can slow down the flying velocity of CO2 snow which are effective methods to control the jet velocity and prevent the risk of penetration.